Major challenges for education in Wales - Luke Sibieta (Institute for Fiscal Studies (IFS), 2024)
This report examines the major challenges for education in Wales, including low outcomes across a range of measures and high levels of inequality.
Keywords: 330; Education and skills; Poverty; inequality and social mobility; Education spending; Devolution; Education; Human capital; Inequality; Schools; Skills